2021
DOI: 10.1159/000514714
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Hyperplastic Polyps: A Benign Entity? Analysis of Recurrence and Neoplastic Transformation in a Cohort Study

Abstract: <b><i>Introduction:</i></b> Hyperplastic polyps represent 30–93% of all gastric epithelial polyps. They are generally detected as innocuous incidental findings; however, they have a risk of neoplastic transformation and recurrence. Frequency and risk factors for neoplastic transformation and recurrence are not well established and are fields of ongoing interest. This study aims to evaluate the frequency of and identify the risk factors for recurrence and neoplastic change of gastric hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…[7,11] In general, GHP occurs in the abnormal background mucosa, particularly in AIG. Stimulated by high levels of gastrin, the association between GHP and AIG is well verified [13] and the data demonstrated that 12% GHP related to AIG. [14] The development of cancer is deemed to a multi-step process through hyperplasia-dysplasia-carcinoma sequence, [15] and AIG confers an increased risk of intestinal-type gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[7,11] In general, GHP occurs in the abnormal background mucosa, particularly in AIG. Stimulated by high levels of gastrin, the association between GHP and AIG is well verified [13] and the data demonstrated that 12% GHP related to AIG. [14] The development of cancer is deemed to a multi-step process through hyperplasia-dysplasia-carcinoma sequence, [15] and AIG confers an increased risk of intestinal-type gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In general, GHP occurs in the abnormal background mucosa, particularly in AIG. Stimulated by high levels of gastrin, the association between GHP and AIG is well veri ed [13] and the data demonstrated that 12% GHP related to AIG [14]. The development of cancer is deemed to a multi-step process through hyperplasia-dysplasia-carcinoma sequence [15], and AIG confers an increased risk of intestinal-type gastric cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate of early cardia cancer has been increasing in recent years, 3,4 together with an elevated detection rate of cardia polyps, which ranges from 0.35% to 0.46% using unsedated and sedated endoscopic examinations 5 . Among all patients with gastric polyps, 11% are found to have cardia polyps 6 . Cardia polyps are defined as pedunculated or sessile lesions that originate from the mucosal epithelium of the cardia that protrude into the cavity 7 .…”
Section: Introductionmentioning
confidence: 99%